2022
DOI: 10.1007/jhep01(2022)025
|View full text |Cite
|
Sign up to set email alerts
|

The tiny (g-2) muon wobble from small-μ supersymmetry

Abstract: A new measurement of the muon anomalous magnetic moment, gμ− 2, has been reported by the Fermilab Muon g-2 collaboration and shows a 4.2 σ departure from the most precise and reliable calculation of this quantity in the Standard Model. Assuming that this discrepancy is due to new physics, we concentrate on a simple supersymmetric model that also provides a dark matter explanation in a previously unexplored region of supersymmetric parameter space. Such interesting region can realize a Bino-like dark matter can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 142 publications
(155 reference statements)
1
19
0
Order By: Relevance
“…We also found that the DM preferred to be heavier than about 300 GeV when we implemented detailed Monte Carlo simulations for the constraints from the latest LHC searches for electroweakinos. These observations significantly improve the conclusions of [77] and [78], since more LHC analyses were considered carefully. be as large as several TeV, because DM-nucleon scattering rates are enhanced by a factor of 1/(1 − m 2 χ0 1 /µ 2 ) 2 as m 2 χ0 1 /µ 2 → 1 (see discussions in Appendix A).…”
Section: Introductionsupporting
confidence: 58%
“…We also found that the DM preferred to be heavier than about 300 GeV when we implemented detailed Monte Carlo simulations for the constraints from the latest LHC searches for electroweakinos. These observations significantly improve the conclusions of [77] and [78], since more LHC analyses were considered carefully. be as large as several TeV, because DM-nucleon scattering rates are enhanced by a factor of 1/(1 − m 2 χ0 1 /µ 2 ) 2 as m 2 χ0 1 /µ 2 → 1 (see discussions in Appendix A).…”
Section: Introductionsupporting
confidence: 58%
“…Extensions of the SM aiming at combined explanations of a µ and (some of) the B physics anomalies have been presented in refs. [29][30][31][32][33][34][35][36][37][38][39][40], The a µ anomaly involves only leptons of the second generation and, taken alone, does not indicate any violation of flavour quantum numbers. It also does not provide a clear indication on the energy scale of the associated new dynamics [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…This new world average points to a 4.2σ deviation from the SM predictions [3][4][5]. The supersymmetric contributions to muon g − 2 arise from a number of super partners which couple to muon at tree-level [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In order to solve this discrepancy, the SUSY electroweak sector should involve relatively light neutralinos, charginos and sleptons.…”
Section: Introductionmentioning
confidence: 99%